Across Culture Adaptation of Santa Clara Religious Belief Scale in Urdu: Religious Belief as a Predictor of Wellbeing and Life Satisfaction during Covid-19 in Pakistan - Komal Saleem; Asmat Ullah; Muhammad Adil; Nabila Raheem; Sifaat Khan Rabbani; Samina Mustafa (Research Journal of Psychology, 2025)
The current study acquired and conducted after extensively studying these variables with the help of literature these hypotheses were formulated to examine in the current study, it was hypothesized that (a) There would be a relationship between religious belief, life satisfaction and psychological wellbeing among Muslim and NON-Muslim group during Covid 19 pandemic. (b) There would be a difference between gender on the basis of religious belief life satisfaction and wellbeing during Covid 19 pandemic (c) on average, people high on religious belief will have better wellbeing and life satisfaction as compare to the people with low religious belief during Covid 19 pandemic. Data was collected through random sampling from 210 participants 115 were males and 95 were female. Participants were between the age range of 16 to 60 with the education level of metric or above. Santa Clara strength of religious faith Questionnaire (Larkey., 1996) for religious belief, satisfaction with life scale (schutte et al., 1998) for life satisfaction and Warwick-Edinburg Mental Wellbeing Scale (WEMWBS) (Tennant, R., Fishwick, R., Platt, S., Joseph, S., Stewart-Brown, S, 2006) for wellbeing has been used to measure. along with demographic form. Data was collected through online Google form and have analyzed through Pearson product moment correlation, Independent sample t-test and regression. The findings of the study show weak significant (P<0.01) relationship between religious belief, life satisfaction and wellbeing with that male scored higher on religious belief and wellbeing as compare to female but both scored similar on life satisfaction with that findings also showed that religious belief is a predictor of better life satisfaction and wellbeing (P<0.05). This study concluded that religious beliefs do influence individual and their psychological wellbeing and life satisfaction. Limitation and implication of the study has been discussed.